Panorama do setor leiteiro antes, durante e depois da pandemia da covid-19 - Vaurof, Marcos Vinicius Ianuxauskas (Universidade Federal de São Carlos, 2024)
Milk is one of the most relevant agricultural commodities, being one of the five most traded products, in volume and value. Currently, Brazil plays a significant role in the production of the product worldwide, occupying third place, behind only the United States and India. Knowing this relevance to national agribusiness, this work sought, through a bibliographic review, to evaluate the impacts of COVID-19 on the panorama of the dairy sector and aimed to evaluate the visible differences in each period, before, during and post-pandemic. The methodology used was research on different references including articles, monographs, theses, periodicals and technical circulars and based on the work of Dias (1994) who evaluated the panorama of the dairy sector according to production, import and export, consumption and market prices. It can be concluded that there were significant changes in all evaluated fields, fulfilling the initially proposed objective.
Overview of the dairy sector before, during and after the COVID-19 pandemic.
Keywords: SARS-CoV; Leite de vaca; Preço do leite; Hábitos de consumo; SARS-CoV; Cow's milk; Milk price; Consumption habits; CIENCIAS AGRARIAS::AGRONOMIA; CIENCIAS AGRARIAS::ZOOTECNIA; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::TECNOLOGIA DE ALIMENTOS::TECNOLOGIA DE PRODUTOS DE ORIGEM ANIMAL; CIENCIAS AGRARIAS::ZOOTECNIA::PRODUCAO ANIMAL